VOICETAINER SEBAGAI PELUANG KERJA BAGI GENERASI MILENIAL DALAM BIDANG KOMUNIKASI DAN PUBLIC SPEAKING - Faisal Muzzammil; Adilah (Mafaza : Jurnal Pengabdian Masyarakat, 2023)
The ability to communicate effectively and good public speaking skills, today is indispensable for various needs, including being used and exploited as job opportunities in the field of communication and public speaking. Against this background of the need for public speaking skills, especially for the millennial generation, a public speaking workshop was held that focused on introducing and practicing voice coaches. The implementation of the public speaking workshop has two main objectives, namely: (1) Get to know the Voicetainers; (2) Practicing Voicetainer. Methodologically, this public speaking workshop activity is carried out using service learning method. At the operational level, the service learning method in this activity is carried out by teaching participants about public speaking by combining academic approaches (voicetainer concepts and theory) and training practical skills (practicing voicetainer) of activity participants in the fields of communication and public speaking which can be used as job opportunities. Specifically, this activity has been carried out well and has achieved maximum results on the following two points: (1) Workshop participants can recognize and know about a voice coach, which is a public speaking skill that can support work in the field of communication; (2) Workshop participants can practically and applicatively practice public speaking skills which can be used as job opportunities in the field of communication.